Desain Lampu Cerdas Berbasis Arduino Nano Untuk Kondisi Bencana - Ajiatmo, Dwi; Malik, Fahad Abdul; Raikhani, Agus (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This research offers the manufacture of an emergency light prototype using Arduino Nano as the main controller. This prototype uses a buck converter in collaboration with an Arduino Nano to regulate the duty cycle with Pulse Width Modulation, based on feedback from voltage and current sensors. MOSFETs are used to regulate the voltage from a 10 Wp solar panel using the PWM method which is controlled by Arduino Nano. This buck converter is an inverting type because it changes the position of the supply voltage. Maximum Power Point Tracking (MPPT) technique is used to optimize energy from solar cells by finding optimal working points, ensuring maximum efficiency. This research also uses a 3.7 V lithium battery with a capacity of 18,650 mAh as a load for a series of prototype lights with the Joule Thief concept. The Joule Thief circuit is a minimalist oscillating voltage amplifier that is economical and easy to make, suitable for driving LED lights or DC dynamos. The results of this research show that the DC-DC MPPT buck converter based on the Arduino nano microcontroller can work well. By setting the duty cycle to 80 percent and a frequency of 62.5 kHz, current and voltage measurements produce an output of 4.95 volts - 5 volts.